PARENTAL INVOLVEMENT IN EARLY CHILDHOOD EDUCATION FOR FAMILY EMPOWERMENT IN THE DIGITAL AGE - Sri Nurhayati (IKIP Siliwangi Bandung, 2021)
Parental involvement in early childhood education plays a vital role in the growth and development of children. Various research results show that parental involvement has a positive impact on parents and educators or managers of PAUD institutions must be in an excellent relationship to meet all children's needs. The aim of this study is to examine the involvement of parents in early childhood education in order to empower families in a digital age that is full of challenges, particularly in the context of the organization of quality early childhood education. This aims to inform parents of the importance of their involvement in the child education process and to establish good communication and collaboration between parents, educators and managers of educational institutions. This research uses a descriptive method of research with a qualitative approach. The research was conducted at TAUD SaQu Nurul Islam Al Husna Kota Cimahi, with the research subjects of 30 parents, 2 educators and 1 managers of PAUD institutions. Collection of data through interviewing techniques, observation and documentation studies. The results showed that: parental involvement in TAUD Saqu Nurul Islam Al Husna includes parenting activities, sharing information between parents and teachers through various communication media, parental volunteering, home learning assistance, involvement in decision-making, and parental participation in field activities. Through a variety of activities involving parents, making it more empowered to build a family force that can be beneficial to the child's success.